If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 5x = 1 + x Solving 9 + 5x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 5x + -1x = 1 + x + -1x Combine like terms: 5x + -1x = 4x 9 + 4x = 1 + x + -1x Combine like terms: x + -1x = 0 9 + 4x = 1 + 0 9 + 4x = 1 Add '-9' to each side of the equation. 9 + -9 + 4x = 1 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 1 + -9 4x = 1 + -9 Combine like terms: 1 + -9 = -8 4x = -8 Divide each side by '4'. x = -2 Simplifying x = -2
| x-33=5x+3 | | x+28=5x+12 | | 9x+10=6x+5 | | n+(n+25)+(n-27)=100 | | 30.25+11-5.5=-28 | | 6x-5=5(x-3) | | x^2+31+x^2=41 | | x-16=4x+11 | | 5x-9=x-3 | | 3x+22=x+6 | | 4+x-3x+2=4x+2-3x+1 | | 3+4x-7+2x=x+4+x | | 2ln(x)=x | | 0.8x=0.5y-2 | | 25r-30=50 | | -5x^2-125=0 | | 4v^2-8v-140=0 | | 93=3x+5 | | 30r+25=50 | | 8n^2-24n=0 | | .6*5= | | 25+30r=50 | | 2(49)+2(128)= | | 93=x+19+3x+5 | | 93=(x+19)(3x+5) | | m^3-m^2n-mn^2+n^3=o | | (4z+1)(4+z)=0 | | -16x^2+175x-85=0 | | -2(x+7)-9=5x+12 | | -16x^2+175-85=0 | | 4x+8-3=4x+29 | | x/62+89=94 |